Megaregulation contested : global economic ordering after TPP - Kingsbury, Benedict (Oxford : Oxford University Press, 2019)
In this collection, leading scholars from around the world analyse 'megaregulation': a new intergovernmental economic ordering and form of governance. In the aftermath of the failure of TPP, the collection also looks at the controversies surrounding megaregulation and the future directions complex transnational governance may take.
This edition also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on June 10, 2019).
Keywords: Trade regulation -- International cooperation; Commercial policy -- International cooperation